The targeting of Lamp1 to lysosomes is dependent on the spacing of its cytoplasmic tail tyrosine sorting motif relative to the membrane (The Rockefeller University Press, 1996)
Lamp1 is a type I transmembrane glycoprotein that is localized primarily in lysosomes and late endosomes. Newly synthesized molecules are mostly transported from the trans-Golgi network directly to endosomes and then to lysosomes. A minor pathway involves transport via the plasma membrane. The 11-amino acid cytoplasmic tail of lamp1 contains a tyrosine-based motif that has been previously shown to mediate sorting in the trans-Golgi network and rapid internalization at the plasma membrane. We studied whether this motif also mediates sorting in endosomes. We found that mutant forms of lamp1 in which all the amino acids of the cytoplasmic tail were modified except for the RKR membrane anchor and the YXXI sorting motif still localized to dense lysosomes, indicating that the YXXI motif is sufficient to confer proper intracellular targeting. However, when the spacing of the YXXI motif relative to the membrane was changed by deleting one amino acid or adding five amino acids, lysosomal targeting was almost completely abolished. Kinetic studies showed that these mutants were trapped in a recycling pathway, involving trafficking between the plasma membrane and early endocytic compartments. These findings indicate that the YXXI signal of lamp1 is recognized at several sorting sites, including the trans-Golgi network, the plasma membrane, and the early/sorting endosomes. Small changes in the spacing of this motif relative to the membrane dramatically impair sorting in the early/sorting endosomes but have only a modest effect on internalization at the plasma membrane. The spacing of sorting signals relative to the membrane may prove to be an important determinant in the functioning of these signals.